Microbial osteolysis in an Early Pleistocene hominin (Paranthropus robustus) from Swartkrans, South Africa. Issue 85 (August 2015) - Grine, Frederick E.; Bromage, Timothy G.; Daegling, David J.; Burr, David B.; Brain, Charles K.
Abstract: Microbiological degradation is one of the most important factors responsible for the destruction of bone in archaeological contexts. Microscopic focal destruction (MFD) is the most prevalent form of microbial tunneling and is encountered very commonly in human bones from archaeological sites, whereas animal bones from these same sites show significantly better preservation if they were deposited in a fragmentary (e.g., butchered) state. Similarly, most fossils show either no evidence or only minor traces of bacterial osteolysis. These observations and experimental evidence point to an endogenous origin for osteolytic bacteria, suggesting that bone bioerosion could potentially aid in reconstructing early taphonomic events. We here report extensive MFD in the mandibular corpus of a small (presumptive female) individual of the hominin Paranthropus robustus from the Early Pleistocene site of Swartkrans, South Africa. The specimen (SKX 5013) derives in situ from the Member 2 deposit, which is dated to ca. 1.5–1.0 Ma. Examination of sections from the corpus by backscattered electron microscopy reveals numerous small linear longitudinal and budded tunneling cavities, which tend to be concentrated around Haversian canals and are more abundant closer to the endosteal aspect of the section. The taphonomy of Swartkrans has been the subject of intense investigation, and given the possibility that different agents of accumulation may have been responsible for the faunal and hominin fossils in the different members at the site, the observation that a specimen of P. robustus from Member 2 displays significant microbial osteolysis is of potential interest. A study of the prevalence of this process in adequately large samples of the animal bones from these units may yield novel insights and provide refinement of our understanding of their taphonomic histories. Such observations might well reveal differences among the various members that could provide another valuable source of osteoarchaeological information for the site.